2013
DOI: 10.1590/s0103-05822013000300009
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein and its relation to high blood pressure in overweight or obese children and adolescents

Abstract: OBJECTIVE To investigate the association between C-reactive protein (CRP) and high blood pressure (BP) in overweight or obese children and adolescents. METHODS Cross-sectional study with 184 overweight or obese children and adolescents aged from two to 18 years old, from April, 2009 to April, 2010. The classification of nutritional status used the body mass index (BMI). Based on the Centers for Disease Control and Prevention curve, individuals were classified as: overweight (BMI between the 85th-95th percentil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 21 publications
2
18
0
5
Order By: Relevance
“…[13][14][15][16][17] In addition, recent clinical investigations continue to provide insight into the proinflammatory mechanisms of disease and morbidities in obesity and diabetes mellitus in children and adults. [18][19][20] Obesity-related morbidities and healthcare costs are increasing 7 while congenital heart surgery outcomes continue to improve. Although this study did not demonstrate a difference in survival after cardiac surgery in those with obesity and/or diabetes mellitus, we did find that these patients had more morbidity and increased hospital utilization than those without obesity and/or diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17] In addition, recent clinical investigations continue to provide insight into the proinflammatory mechanisms of disease and morbidities in obesity and diabetes mellitus in children and adults. [18][19][20] Obesity-related morbidities and healthcare costs are increasing 7 while congenital heart surgery outcomes continue to improve. Although this study did not demonstrate a difference in survival after cardiac surgery in those with obesity and/or diabetes mellitus, we did find that these patients had more morbidity and increased hospital utilization than those without obesity and/or diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…26 hsCRP seviyelerinin de diğer faktörlerden bağımsız olarak hipertansif hastalarda yükseldiği gösterilmiştir. [27][28][29] Çalışmamızda hsCRP ve Lp(a) değerleri evre 2 hipertansiyonlu grupta anlamlı olarak daha yüksek bulundu. Tüm hasta grubunda inflamasyon parametreleri yüksek olan hastaların fonksiyonel olarak KVS değişikliklerinin diğer gruba göre daha fazla olduğu saptandı.…”
Section: Discussionunclassified
“…C-reactive protein (CRP) is an inflammatory marker and is considered a marker for atherosclerosis. Although two studies found a significant association between CRP and blood pressure in obese children, independently of BMI (62,63), one study did not (64).…”
Section: Inflammationmentioning
confidence: 94%